Most Prevalent Diseases in Chambal Region and Available Vegetation useful for Treatment - Kondalkar, Sapna Avinash (International Journal of Pharmaceutical & Biological Archive, 2022)
The prices of medicines and pharmaceuticals are unaffordable for most of the population of developing countries. Rational and effective use of locally available plants may serve a solution. Determination of possible role of native vegetation in the management of prevalent diseases in the studied area was the basic concept. Hence, vegetation, their occurrence and the most prevalent diseases of the region were observed and recorded. The observations supported the hypothesis and it was found that, there are many plants which may be useful in the management of prevalent diseases in studied area.